Management of Onion Thrips (Thrips Tabaci) Using Different Eco-friendly Management Approaches (SAARC Journal of Agriculture, 2026)
Onion (Allium cepa L.), also known as the bulb onion or common onion is an important spicy vegetable that are used as food and medicinal purpose. It is infested by several types of insect pests that reduce the yield of onion. With a view to develop eco-friendly management approaches against onion thrips, a field experiment was conducted at the research farm of Sher-e-Bangla Agricultural University, Dhaka, during the Rabi season in 2023-24. The experiment followed a randomized complete block design (RCBD) with ten treatments, each replicated three times. The treatments were T1= onion intercropped with carrot, T2= onion intercropped with coriander, T3= onion intercropped with tomato, T4= onion + blue sticky trap, T5= onion + white sticky trap, T6= neem oil spray at 7-day interval, T7= Spirotetramat spry at 7-day interval, T8= Abamectin spray at 7-day interval, T9= Spinosad at 7-day intervals, and T10= control. All treatments significantly reduced the thrips population and leaf infestation caused by thrips compared to the untreated control. The lowest thrips population (1.30 thrips/plant at 51 DAT, 2.20 thrips/plant at 100 DAT and cumulative mean population (2.20), percent reduction of thrips population over control (76.79%) and minimum leaf infestation (19.13% at 100 DAT, cumulative mean infestation (13.28%), and percent reduction of leaf infestation over control 64.36%) were observed in the plot treated with Spinosad and returned the highest bulb height (5.79 cm), bulb width (7.71 cm), bulb weight (45.00 g), and yield (18.33 t/ha). Besides, the results from correlation coefficient indicated that some parameters (thrips population and percent leaf infestation) are shown significantly negative correlation with yield and some parameters (thrips population) are significantly explored positive with percent leaf infestation. Therefore, the findings of present study suggest that applying Spinosad at seven-day interval from the initial thrips infestation is an effective strategy for managing thrips in onions.SAARC J. Agric., 23(2): 159-171 (2025)